Design of Biped Robots: A Review - Saakshi Aeron; Sofi Fatima; Amanpreet Singh3 (International Journal of Mechanical Dynamics and Systems Analysis, 2024)
Biped robots, inspired by the human’s kinematic structure, have seen remarkable evolution from early mechanical automata to today’s sophisticated machines capable of performing complex tasks. Their design aims to achieve efficient and stable movement on two legs. This paper examines the current advancements and historical progress in the development of bipedal robots. The authors investigate the implementation of these robots in various fields, like healthcare, entertainment, search and rescue operations, and industrial automation, emphasizing their potential to transform multiple industries. In addition, the current work dives deeply into bipedal locomotion (kinematics), dynamic walking (dynamics), and control strategies that are scrutinized, revealing how algorithms and feedback mechanisms are employed to achieve stability and agility. Further, various design aspects like actuation, feedback control, sensors, and perception are discussed. Furthermore, various biped robots have been compared based on their design, mechanics, actuation, sensor and perception, performance metrics, and control strategies. Moreover, based on the findings of the present work, the possible research gaps are identified and near-future research directions are formulated. The principle idea is to enhance the design and development of biped robots, highlighting their potential to revolutionize various aspects of our lives. This manuscript reviewed 44 papers summarizing the advancements, reported from 1998 to 2024, in biped robotics. The authors believe that this information will act as a key resource for researchers working in the mentioned field. Finally, based on the proposed work concluding remarks have been made.
Keywords: Biped Locomotion; Biped Robots; Robotics; actuators; human gait; sensors